2017
DOI: 10.5194/amt-10-3589-2017
|View full text |Cite
|
Sign up to set email alerts
|

Tropospheric products of the second GOP European GNSS reprocessing (1996–2014)

Abstract: Abstract. In this paper, we present results of the second reprocessing of all data from 1996 to 2014 from all stations in International Association of Geodesy (IAG) Reference Frame Sub-Commission for Europe (EUREF) Permanent Network (EPN) as performed at the Geodetic Observatory Pecný (GOP). While the original goal of this research was to ultimately contribute to the realization of a new European Terrestrial Reference System (ETRS), we also aim to provide a new set of GNSS (Global Navigation Satellite System) … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 33 publications
4
18
0
Order By: Relevance
“…At this level of accuracy it is difficult to say which of ERAInterim or GPS is biased in an absolute sense. We note however, that the sign and magnitude of the bias are consistent with other studies (Dousa et al, 2017). The standard deviations of differences are about 10-11 mm, which is significantly larger than differences between GPS solutions (as also noticed in previous studies, e.g.…”
Section: Ztd Screening and Comparison To Era-interimsupporting
confidence: 76%
See 2 more Smart Citations
“…At this level of accuracy it is difficult to say which of ERAInterim or GPS is biased in an absolute sense. We note however, that the sign and magnitude of the bias are consistent with other studies (Dousa et al, 2017). The standard deviations of differences are about 10-11 mm, which is significantly larger than differences between GPS solutions (as also noticed in previous studies, e.g.…”
Section: Ztd Screening and Comparison To Era-interimsupporting
confidence: 76%
“…The standard deviations of differences are about 10-11 mm, which is significantly larger than differences between GPS solutions (as also noticed in previous studies, e.g. Dousa et al, 2017). The mean correlation 20 coefficients are about 0.975 for all three variants.…”
Section: Ztd Screening and Comparison To Era-interimsupporting
confidence: 48%
See 1 more Smart Citation
“…However, as a consequence of the significant improvements in GPS processing algorithms, inconsistencies in long‐term time series have been introduced; therefore, there is a need for a homogeneous set of data for GPS meteorology. In this sense, the GPS community has contributed with reprocessed data that are useful for many applications (Dousa et al, ; Pacione & Di Tomaso, ).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have been developed and showed that horizontal gradients from ECMWF (European Centre for Medium‐Range Weather Forecasts) and water vapor radiometers (WVR) do agree with GPS‐estimated ones at the level of 0.5 mm for ECMWF and with a correlation of about 50% with WVR. See, for instance, Kačmařík et al (), Dousa et al (), Lu et al (), Li et al (), and Bar‐Sever et al (). Morel et al () have studied the behavior of the tropospheric gradients in Corsica island and have found that they can be influenced by both the slope of the relief and land/sea contrast in a mean year behavior.…”
Section: Introductionmentioning
confidence: 99%